Design and implementation of a specific strength program for badminton - Sturgess, S.; Newton, R. U. (Strength and Conditioning Journal, 2008)
Badminton is an explosive sport whereby performance can be enhanced from resistance training. Effective resistance training programming requires a systematic process of analysis, implementation and evaluation to ensure maximum adaptation and improvement. This article focuses on the prescription of resistance training methods targeted for badminton specific performance enhancement and the implementation of badminton specific exercises into a pre competition or competition phase of a periodized plan.